2016
DOI: 10.1021/acs.biochem.6b00703
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Reactive Oxygen Species and Exotic DNA Lesions as an Exploitable Liability

Abstract: Although the terms “excessive reactive oxygen species (ROS)” and “oxidative stress” are widely used, the implications of oxidative stress are often misunderstood. ROS are not a single species but a variety of compounds, each with unique biochemical properties and abilities to react with biomolecules. ROS cause activation of growth signals through thiol oxidation and may lead to DNA damage at elevated levels. In this review, we first discuss a conceptual framework for the interplay of ROS and antioxidants. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 137 publications
(276 reference statements)
0
43
0
Order By: Relevance
“…[13,14] The interaction of plasma with cells may result in the oxidation of macromolecules and proteins, peroxidation of lipids, and damage to DNA which eventually interrupts cell signaling and metabolic processes. [15,16] The RONS produced by LTPs can increase the cells' oxidative stress leading to growth inhibition or cell death. [17][18][19] Many investigations have shown that there is a correlation between plasma produced RONS levels and cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] The interaction of plasma with cells may result in the oxidation of macromolecules and proteins, peroxidation of lipids, and damage to DNA which eventually interrupts cell signaling and metabolic processes. [15,16] The RONS produced by LTPs can increase the cells' oxidative stress leading to growth inhibition or cell death. [17][18][19] Many investigations have shown that there is a correlation between plasma produced RONS levels and cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive ROS may induce DNA damage resulting in cancer cell apoptosis . Given differential responses of ROS modulating drugs and natural products between cancer and normal cells, selective DNA damage for selective apoptosis and killing may occur in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…2 Therefore, several ROS modulating drugs and natural products have been developed to achieve oxidative stressbased selective cell killing for anticancer therapy. [3][4][5][6][7][8] Excessive ROS may induce DNA damage 9 resulting in cancer cell apoptosis. 10,11 Given differential responses of ROS modulating drugs and natural products between cancer and normal cells, 1 selective DNA damage for selective apoptosis and killing may occur in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The HO . has sufficient oxidizing power to abstract an electron from a guanine base or from the ribose C−H bond, and this leads to DNA damage (Figure , black) . In this manuscript, we report a reagent that selectively eliminates HO .…”
Section: Figurementioning
confidence: 93%
“…Among DNA bases, guanine has the lowest redox potential. Under severe oxidative stress, guanine is oxidized to hyperoxidative lesions that are cytotoxic and mutagenic . One such lesion is 2,2,4‐triamino‐2 H ‐oxazol‐5‐one‐2′‐deoxyribonucleoside (dZ, oxazolone).…”
Section: Figurementioning
confidence: 99%